Dielectric and Electrical Properties of WS2 Nanotubes/Epoxy Composites and Their Use for Stress Monitoring of Structures. (4th May 2017) - Sedova, A.; Khodorov, S.; Ehre, D.; Achrai, B.; Wagner, H. D.; Tenne, R.; Dodiuk, H.; Kenig, S.
Abstract : The dielectric and electrical characteristics of the semiconductive WS2 nanotubes/epoxy composites were studied as a function of the nanotubes concentration and the pressure applied during their molding. In addition, the ability of WS2 nanotubes to serve as stress sensors in epoxy based nanocomposites, for health-monitoring applications, was studied. The nanocomposite elements were loaded in three-point bending configuration. The direct current was monitored simultaneously with stress-strain measurements. It was found that, in nanocomposites, above the percolation concentrations of the nanotubes, the electrical conductivity increases considerably with the applied load and hence WS2 nanotubes can be potentially used as sensors for health monitoring of structural components.